Effect of Exercise Repetitions on Arylesterase Activity of PON1 in Plasma of Average-Trained Men-The Dissociation between Activity and Concentration - Aneta Otocka-Kmiecik; Monika Orłowska-Majdak; Robert Stawski; Urszula Szkudlarek; Gianluca Padula; Szymon Gałczyński; Dariusz Nowak (MDPI AG, 2023)
Exercise may increase the antioxidant capacity of plasma by stimulating antioxidant enzymes. The study aimed to measure the effect of three repetitions of acute exercise on arylesterase (ARE) activity of the paraoxonase 1 (PON1) enzyme. Eleven average-trained men (age 34.0 ± 5.2 years) completed three treadmill runs. ARE activity in plasma was evaluated spectrophotometrically and compared with PON1 concentration (PON1c), paraoxonase (PON) activity, and high-density lipoprotein cholesterol (HDL-C) at rest and after exercise. In all repetitions of the exercise, ARE activity remained stable, and ARE activity standardized for PON1c (ARE/PON1c) was lower post- than pre-exercise. The ARE/PON1c ratio changes returned to baseline levels during rest after each exercise session. Pre-exercise ARE activity correlated negatively with post-exercise C-reactive protein (CRP) (ρ = −0.35, p = 0.049), white blood cell count (WBC) (ρ = −0.35, p = 0.048), polymorphonuclear leukocytes (PMN) (ρ = −0.37, p = 0.037), and creatine kinase (CK) (ρ = −0.37, p = 0.036). ARE activity may be depleted under conditions of oxidative stress, as increases in PON1c during acute exercise did not result in parallel increases in ARE activity. No adaptation of the response of ARE activity to exercise was detected in subsequent exercise sessions. Individuals with lower pre-exercise ARE activity may develop a higher inflammatory response to strenuous exercise.